Virtual Models for Real-World Learning: The Development and Evaluation of a Patient Simulator for Eye Disability Diagnosis - Muhammad Khuarizmi bin Mohd Rapi (Universiti Sains Islam Malaysia, 2024)
Matric: 3212459 (FST)